Development of a communication book for children with cerebral palsy and communication disorders using the partner assisted scanning method: A pilot study - Pappring, Worakanok; Chinchai, Supaporn (Journal of Associated Medical Sciences, 2023)
Background: Cerebral Palsy (CP) is a physical disability impacting movement, posture, and communication. For children with CP and severe communication challenges, methods like Partner Assisted Scanning (PAS) are invaluable. Despite its effectiveness, research on PAS in the context of Thailand is scarce. Objectives: This study aimed to develop and validate a communication book and related materials for children with CP, utilizing the PAS method. Additionally, the study aimed to analyze communication partners’ satisfaction levels with the communication book. Materials and methods: The study involved two phases. First, four instruments were developed and assessed for content validity: The communication Abilities Assessment, the Communication Partners’ Satisfaction Survey, the Communication Book Manual, and the Communication Book. In the second phase, these instruments were tested with three families, evaluating partner satisfaction and addressing encountered issues. Results: The study demonstrated high content validity of the communication book (overall validity index=0.97) as assessed by specialists. Feedback highlighted concerns about the book’s format and the time needed for children to grasp its usage. However, communication partners expressed overall high satisfaction (mean=4.67, SD=0.49). Conclusion: This pilot study establishes the robust content validity of the communication book developed using the PAS method. Moreover, it underscores high satisfaction levels among communication partners, affirming the potential of the communication book to enhance communication skills in children with CP.